Encyclopedia of giftedness, creativity, and talent - Kerr, Barbara A. (Sage Publications, 2009)
Educators have begun to recognize that identifying and accommodating students who are slower to learn may leave behind those who learn rapidly and think creatively. The nature of intelligence, the sources of innovation, and the ways to nurture special abilities are now topics of great interest to scholars in a wide variety of disciplines and to the general public